Yield performance of Ficus carica as affected by different rate of chicken manure - Shamsuddin, M.S.; Shahari, Rozilawati; Che Amri, Che Nurul Aini; Tajudin, Nur Shuhada (Agricultural Research Communication Centre, India, 2020)
The objectives of this study are to study the development of the fruit of Ficus carica as affected by the different rates of chicken manure. The experiment was conducted at Glasshouse and Nursery Complex (GNC), IIUM Kuantan Campus. The experiment was arranged in a randomized, completely block design (RCBD). Four rates of chicken manure used were 0 g (T1), 150 g (T2), 300 g (T3) and 450 g (T4) respectively. Based on this study, it showed that there was a significant difference between treatments on all parameters collected. From all parameters, thirteen parameters showed the highest value from treatment consist of 450 g of chicken manure (T4). Meanwhile, no fruit produces from treatment with no fertilizers applied (T1). This indicates that higher performance was produced from the greater amount of chicken manure used. So, it was recommended to increase chicken manure rate on fig to increase yields productivity.